Advances in the diagnosis and classification of systemic lupus erythematosus. (1st December 2016) - Larosa, Maddalena; Iaccarino, Luca; Gatto, Mariele; Punzi, Leonardo; Doria, Andrea
ABSTRACT: Introduction : Systemic lupus erythematosus (SLE) is the prototype of systemic autoimmune diseases. Patients with SLE display a wide spectrum of clinical and serological findings that can mislead and delay the diagnosis. Diagnostic criteria have not been developed yet, whereas several sets of classification criteria are available; however, none of them has 100% sensitivity and 100% specificity, i.e. the hallmark of diagnostic criteria. Nevertheless, classification criteria are often misused as diagnostic criteria, which may affect earliness of diagnosis and lead to more misdiagnosed cases. Areas covered : In this review, we compare old and new classification criteria, discussing their application and pinpointing their limitations in the management of patients. Moreover, we will focus on current and novel biomarkers for SLE diagnosis, highlighting their predictive value and applicability in clinical practice. Expert commentary : SLE diagnosis still represents a challenge, remaining largely based on a clinical judgment. Besides SLE diagnosis, even its classification is still challenging to date. Indeed, although classification of SLE seems to be achieved more frequently with the 2012 SLICC criteria than with the previous 1997 ACR criteria, this last-updated 2012 set might be improved. Notably, diagnostic and classification criteria should be applied to any subject in the world, and consequently they should include immunological variables validated in different populations, which is still an unmet need.